Gender and contemporary horror in television - Gerrard, Steven, 1970-; Holland, Samantha; Shail, Robert (Emerald studies in popular culture and gender., 2019)
Horror has found a resurgence on television in the post-millennial years. This book will investigate the changing and challenging roles that gender has undergone in TV horror, examining a range of shows, includingHannibal, American Horror Story, The Walking Dead, Penny Dreadful, Supernatural, The Exorcist, iZombie, and Bates Motel.